From Papers to Practices: Embracing Challenges of ISO Certification - Reyteran, Riza (JPAIR Multidisciplinary Research, 2021)
As a mechanism to ensure quality education and services in the state colleges and universities in the Philippines, ISO certification entails embracing challenges and adopting strategies for the sustainable implementation of quality management systems, policies, and procedures. This descriptive study looked into the strategies employed, the challenges encountered and the changes observed by one state college during ISO certification. A total of 84 college officials, faculty members, and staff were requested to answer a questionnaire. Responses were validated through an interview among selected participants. Results revealed the respondents’ positive perception towards ISO certification; the institution’s employment of consultant, conducting seminars, trainings, internal audits, and management review, and implementation of ISO-aligned policies and procedures as strategies; conduct of orientations, dissemination of information, time management, provision of necessary resources and commitment of top management to address challenges on lack of awareness, resistance to change, conflict in schedule, insufficient knowledge on ISO standards and implementation of policies and procedures; and improvement in the school image, customer satisfaction, communication, and implementation of policies and procedures as observed changes. Hence, the respondents’ perception, strategies, and actions to address the challenges helped the institution acquire and benefit from ISO certification.
Keywords: Social Science; ISO certification; descriptive design; Philippines